1999
DOI: 10.1182/blood.v93.4.1355
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of ETV6 to Neurotrophin-3 Receptor TRKC in Acute Myeloid Leukemia With t(12;15)(p13;q25)

Abstract: Chromosome translocations involving band 12p13 are known to be involved in a variety of hematologic malignancies, some of them resulting in rearrangement of the ETV6/TEL gene. Applying the fluorescence in situ hybridization (FISH) method, we found a cryptic translocation t(12;15)(p13;q25) in an adult acute myeloid leukemia (AML) patient. Hybridization with cosmid probes showed that the ETV6 gene was rearranged in this translocation. A patient-specific cDNA library was screened with ETV6 cDNA, and a novel fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 240 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…31 A shorter variant, in which exon 4 of ETV6 is fused to NTRK3, has been identified in patients with of AML and chronic eosinophilic leukemia. 32,34 Here, we report the occurrence of ETV6-NTRK3 rearrangements in radiation-related and sporadic PTCs, with fusion points that differ from those previously identified in other tumor types because they lack exon 13 of NTRK3.…”
Section: Etv6-ntrk3 Fusion In Thyroid Cancer/leeman-neill Et Almentioning
confidence: 69%
See 1 more Smart Citation
“…31 A shorter variant, in which exon 4 of ETV6 is fused to NTRK3, has been identified in patients with of AML and chronic eosinophilic leukemia. 32,34 Here, we report the occurrence of ETV6-NTRK3 rearrangements in radiation-related and sporadic PTCs, with fusion points that differ from those previously identified in other tumor types because they lack exon 13 of NTRK3.…”
Section: Etv6-ntrk3 Fusion In Thyroid Cancer/leeman-neill Et Almentioning
confidence: 69%
“…The fusion between the ETV6 gene on chromosome 12 and the NTRK3 gene on chromosome 15 was first described in congenital fibrosarcoma in 1998. 31 Since then, ETV6-NTRK3 rearrangements have been identified in several other tumor types, including acute myeloid leukemia (AML), 32,33 chronic eosinophilic leukemia, 34 congenital mesoblastic nephroma, 35 secretory breast carcinoma, 36 and mammary analog secretory carcinoma of the salivary gland. 37 ETV6, also known as TEL, is a transcription factor from the ETS transcription factor family, which is involved in various oncogenic gene fusions resulting from chromosomal translocations, mostly reported in subtypes of AML.…”
Section: Discussionmentioning
confidence: 99%
“…A submicroscopic t(12;15)(p13;q25) resulting in the fusion gene ETV6-NTRK3 on der(15) was thus documented. Moreover, RNA isolated from the BM sample was subjected to reverse transcriptase-PCR using primers designed to amplify either the 731-bp solid cancer ETV6-NTRK3 variant (5) or the 601-bp acute myeloid leukaemia (AML) ETV6-NTRK3 variant (6). These latter molecular analyses demonstrated the 731-and 1265-bp products, respectively, as expected when the solid cancer-associated fusion transcript is detected ( Fig.…”
Section: Chronic Eosinophilic Leukaemia With Etv6-ntrk3 Fusion Transcmentioning
confidence: 72%
“…Lanes 1-4 and lane 7 refer to negative controls and molecular weight markers, respectively. (6). Neither ETV6-NTRK3 variant has subsequently been detected in a molecular screen of BM samples collected from 13 and 58 children affected with either AML or acute lymphoblastic leukaemia, respectively (10).…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…TEL was ®rst discovered as the target of a chromosomal rearrangement in a chronic myelomonocytic leukemia patient (Golub et al, 1994), and chromosomal translocations involving TEL have since been found in a large number of additional hematological malignancies (Rubnitz et al, 1999). These genetic rearrangements result in a variety of oncogenic TEL chimeras, most of which fuse the SAM domain of TEL to a variety of tyrosine kinase domains such as PDGFRb, ABL, JAK2 and NTRK3 (Golub et al, 1994Papadopoulos et al, 1995;Peeters et al, 1997;Knezevich et al, 1998;Eguchi et al, 1999;Lacronique et al, 2000), or to transcription factors such as AML1 and ARNT (Golub et al, 1995;Romana et al, 1995;Salomon-Nguyen et al, 2000). In the tyrosine kinase fusions, TEL±SAM-mediated oligomerization leads to the constitutive activation of the enzyme and is essential for cell transformation (Carroll et al, 1996;Golub et al, 1996;Jousset et al, 1997;Lacronique et al, 1997).…”
Section: Introductionmentioning
confidence: 99%